Migraciones inducidas por el cambio climático: un análisis del marco de asociación país España-Senegal desde la coherencia de políticas para el desarrollo - Alexis Cloquell-Lozano; Isabel Royo-Ruiz; María Isolda Perelló-Carrascosa; Beatriz Felipe-Pérez (Revista Iberoamericana de Estudios de Desarrollo)
The inclusion of the principle of Policy Coherence for Development (PCD) into the 2030 Agenda and its interrelation with climate induced migration constitutes both a challenge and a commitment for the Spanish foreign policy in addressing the challenges posed by Africa, specifically in the case of Senegal. In this context, the objective of this article is to analyze the degree of alignment between the Spanish development cooperation policy and the Senegal’s National Development Strategies from the perspective of PCD, particularly in relation to issues linked climate induced migration. The results highlight a lack of alignment in the policies of both countries regarding these issues. These discrepancies are influenced by political, geostrategic, and commercial interests within the Africa Plan.